APPRAISAL OF THE QUALITY OF FABRICS MADE OF COMBED WOOL YARNS THROUGH SYNTHETIC INDICES - HRISTIAN Liliana; BORDEIANU Demetra Lăcrămioara; VÎLCU Cătălin (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2015)
In order to assess the quality level, it is necessary to determine a series of indices, then to establish the reference elements on whose basis to formulate the findings and the conclusions, thus highlighting the optimum variants of fabrics. In this work have been determined the values of synthetic durability indices, setting the basis for a ranking of studied fabric variants in terms of surface characteristics. The highest weight in this work belongs to the measurement applied to an important number of quality characteristics, representative for the appraisal of durability functions specific to fabric surfaces. The selection of the representative characteristics: breaking strength, Pr (daN); mass loss due to friction stress, Δm (%); thickness diminution due to friction stress, Sg (%), breaking strain work, Ws (daN/m), fabric strength per denier, τt (cN/tex) and wrinkle recovering angle α (o), on whose basis the durability indices were calculated, have been determined through standardized means and methods. The expertise method has been applied to assess the significance degree of the characteristics which express the analyzed products functions. Quality index is the relative expression of a certain characteristic, obtained by referring it to a reference value (norm, standard or pattern). The index can be converted in marks, namely by convention the qualificative/mark «0» represents an inadequate product/non-quality, while the qualificative/mark «1» represents the high qualificative/mark level. In terms of complexity, quality indices can be simple, synthetic and global. The work sets the accent on the appraisal of quality level of the analyzed textile surface by means of synthetic indices.